Menentukan pH Optimum Di DO Stage Untuk Mengurangi Konsumsi CIO2 Pada Proses Pulp Bleaching Di PT. RAPP - Winarto Tarigan; Chairul Chairul; Maria Peratenta Sembiring (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The process of bleaching is a chemical process that is used on chemically treated pulp and mechanical pulp aimed at increasing degrees of brightness according to the expected target. The purpose of the bleaching process are: increasing the brightness, maintaining brightness stability, removing dirt and unwanted components and maintain the physical strength of the pulp. Pulp bleaching process has several stages of the first delignification (D0), Extraction Peroxide (EP), and Last Delignification (D stage). There are few process variables having an effect on the bleaching process, one of which is pH. At first delignification process (D0) with the kappa factor 0.25, the process temperature about 75 oC for 1 hour, the expected optimum end pH is 3.5 to 4.0. In these conditions will produce pulp with 65.42% ISO brightness, and after going through the process of extraction Peroxide (EP) for 90 minutes will produce a pulp with a kappa number a low of 2.63. So after going through the process in Last Delignification (Dstage) will have the lowest consumption of chlorine dioxide. Overall pulp with a final pH Do stage 3.5 to 4.0 Chlorine dioxide is consumed as much as 133.6 ml. Keywords: pH, Bleaching, Chlorine Dioxide